PTU-239 Safety of laparoscopic peritoneal lavage for diverticulitis: outcomes from a dedicated emergency surgery service. (22nd June 2015) - Rhodes, K; Jenkins, D; Qiu, S; Tan, E; Behar, N
Abstract : Introduction: A dedicated emergency surgery service allows for faster accumulation of experience in procedures that are otherwise infrequent; laparoscopic peritoneal lavage (LPL) of perforated diverticulitis is one such procedure. We describe our experience with LPL in a series of consecutive patients treated by such service. Method: Data was collected on 28 consecutive patients undergoing this novel technique in our unit between 2011 and 2014; this was analysed on an intention to treat basis. Outcomes assessed included morbidity, mortality and requirement of further interventions. All patients requiring surgery underwent initial laparoscopy based on our management algorithm. Results: Of the 28 patients included in the study, there was a male:female ratio of 1.5:1 and a mean age of 57 years. Overall 4 patients required conversion to open Hartmann's procedure for Hinchey grade IV. Of the remaining 24 patients, 8 (33%) were classified Hinchey grade I, 9 (38%) as grade II and 7 (29%) as grade III. Concomitant small bowel obstruction was relieved laparoscopically in 6 (25%) patients undergoing LPL and in 2 (50%) patients requiring a Hartmann's procedure. Early results (within 30 days): All 8 Hinchey I patients resolved with intravenous antibiotics and intra-operative drain insertion. Of the Hinchey II and III patients, 3 (19%) required early re-intervention for pelvic abscess formation, all amenable to interventional radiological (IR) drainage. One Hinchey II patient subsequently required resection, despite IR drainage, at 1 week post LPL (failure rate 4%). 30-day mortality was 0% across all Hinchey grades. Late results (Median follow up 26 months): A further 4 of 23 (17%) patients required resection; 2 of these were for malignancy. Only 2 of 19 (11%) patients remaining re-presented with diverticulitis. All patients who underwent Hartmann's for Hinchey grade IV required further operative procedures: 2 emergency and 2 elective. Mortality was 14% across all Hinchey grades. Conclusion: Laparoscopy with a view to washout on an intention to treat basis appears safe, across all Hinchey grades of diverticulitis. LPL also allows laparoscopic relief of small bowel obstruction in patients presenting with this complication of diverticulitis. Further radiological drainage after LPL in this study appears safe although 1 of 3 patients progressed to a Hartmann's procedure. Based on our findings of subsequent malignancy in two patients, we would advise timely post-operative colonoscopy and follow up in all patients. Disclosure of interest: None Declared.